Pengaruh Harga dan Promosi Live Straeming Penjualan Terhadap Perilaku Impulse Buying Pada Pembelian Produk di TikTok Shop - dewi, Ida Ayu Kusuma; Kusuma, Putu Sri Arta Jaya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Online shopping platforms in Indonesia continue to develop with the help of many digital consumers. This requires innovation and good marketing strategies, especially in price and promotion. This research aims to review the influence of price and promotion variables on purchase intention on one of the digital platforms (TikTok Shop). Quantitative methods are used in this study, including data collection techniques, such as distributing questionnaires to 100 respondents. The data collected were then analyzed through multiple linear regression. This research proves that price has a positive but insignificant effect on the impulse buying behavior of TikTok Shop consumers. This means that even though the price is relatively cheap, TikTok Shop consumers are not interested in buying the product. Then, in the second hypothesis, the results showed that live-streaming promotions affect consumer impulse-buying behavior because impulse-buying behavior is driven by the desire to buy a product after the product is marketed through live-streaming. Therefore, live streaming affects impulse buying.